Integrated nutrient management in turmeric (Curcuma longa L.) cv. GNT-2 - Bhat, P. P. Manasa; Bhalerao; Tandel, B. M. (Journal of Plantation Crops, 2023)
The present experiment was carried out, with a view to study the “Integrated nutrient management in turmeric (Curcuma longa L.) cv. GNT-2” during kharif season of the year 2021-22 at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, Gujarat, India. The experiment was conducted in randomized block design (RBD) which included ten treatments and three replications consisting viz., T1: RDF (FYM @ 20 t/ha + 60:60:60 NPK kg/ha), T2: FYM 15 t/ha + 75 % RDF, T3: FYM 20 t/ha + 50 % RDF, T4: Vermicompost 10 t/ha + 75 % RDF, T5: Vermicompost 15 t/ha + 50 % RDF, T6: Bio-compost 10 t/ha + 75 % RDF, T7: Bio-compost 15 t/ha + 50 % RDF, T8: FYM 15 t/ha + 50 % RDF + Novel organic liquid nutrients 5 %, T9: Vermicompost 10 t/ha + 50 % RDF + Novel organic liquid nutrients 5 % and T10: Bio-compost 10 t/ha + 50 % RDF + Novel organic liquid nutrients 5 %. The results revealed that growth parameters i.e. plant height (29.71 cm), number of leaves (5.20), length of leaf (25.15 cm) and breadth of leaf (10.39 cm) were recorded maximum at 45 days after planting when the plots are treated with T1: RDF (FYM @ 20 t/ha + 60:60:60 NPK kg/ha). Among the all treatments, application of FYM 15 t/ha + 50 % RDF + Novel organic liquid nutrients 5 % (T8) gave the maximum plant height (62.78 cm, 130.13 cm and 135.47 cm), number of tillers per plant (1.60, 3.43 and 5.22), number of leaves per plant (7.08, 9.77 and 12.27), length of leaf (32.65 cm, 58.50 cm and 81.21 cm) and breadth of leaf (12.13 cm, 14.44 cm and 18.09 cm) at 75, 135 and 195 DAP, respectively.In case of yield and yield attributes, the maximum number of mother rhizomes per plant (3.54), number of fingers rhizomes per plant (18.57), weight of mother rhizomes (53.26 g per plant) and fresh rhizomes yield (317.80 g per plant and 34.26 t per ha) were observed under the application of FYM 15 t/ha + 50 % RDF + Novel organic liquid nutrients 5 % (T8). Quality aspects viz., curcumin content (4.93 %) and essential oil (3.67 %) were found significantly higher in T9 (Vermicompost 10 t/ha + 50 % RDF + Novel organic liquid nutrients 5 %). Regarding economics, the highest benefit cost ratio (3.77) and the maximum net realization (Rs.6,76,970/ha) was obtained under FYM 15 t/ha + 50 % RDF + Novel organic liquid nutrients 5 % (T8). Moreover, application of FYM 20 t/ha+ 50 % RDF (T3) improved the soil nutrient status.